RANCANG BANGUN ANTENA MIKROSTRIP MEANDER LINE DENGAN MATERIAL FR-4 UNTUK SISTEM GPS TRACKER - Basyar, Muhammad Aditiya Choirun; Kurniawan, Dwi Fadila; Purnomo, Muhammad Fauzan Edy (Jurnal Mahasiswa TEUB, 2024)
Vehicle monitoring system or tracking system is a system that can be used to assist vehicle owners in monitoring the movement of their vehicles remotely. In the tracking system, the antenna acts as a transmitter of radio waves through the LoRa module. Antenna specifications can affect the transmission of radio frequency signals to the LoRa gateaway. This research designs a meander-line microstrip antenna as the transmitter antenna of the GPS Tracker system. Microstrip antennas have advantagesincluding thin cross-sectional area, easy fabrication, small size and light weight, and can be integrated with existing wireless communication devices. This microstrip antenna design will send data to the LoRa gateaway in the 915 MHz frequency range. There are two meander line antennas tested, namely meander line 9 and meander line 11. The meander line 9 antenna produces return loss measurements of -22.162 dB, VSWR of 1.169, and group delay of -13 ns. Meanwhile, the meander line 11 antennaproduced parameter measurements, namely return loss of -27.167 dB, VSWR of 1.092, and group delay of 194.05 ns. Keywords: Microstrip antenna, Meander line antenna, LoRa frequency, Antenna specifications